Outbreak of Guillain-Barre syndrome in Perú - Díaz-Soto, S. (2019)
Guillain-Barre syndrome (GBS) is the most common and most severe acute paralytic neuropathy with an annual incidence of 0.5 to 2 per 100, 000 inhabitants. It can affect people of all ages, but it is more frequent in adults and in males [1,2]. The specific cause of GBS is still unknown; however, its development is associated with previous respiratory or gastrointestinal infections or another pathology in which the immune system attacks the peripheral nerves [2]. GBS has no cure, but an adequate treatment can improve symptoms and shorten its duration (more than 90% of patients can recover completely one year after the onset of the disease); whereas few cases are fatal (mortality rate of 3–7%) [2,3].